XPS STUDY OF REDUCTIVE DISSOLUTION OF BIRNESSITE BY OXALATE: RATES AND MECHANISTIC ASPECTS OF DISSOLUTION AND REDOX PROCESSES - THE EFFECT OF PH AND LIGHT - Banerjee D.; Nesbitt H.W. (My University, 1999)
Reductive dissolution of synthetic 7#9-birnessite [MnO1.7(OH)0.25 or MnO1.95] by Na-oxalate produces a Mn(III) intermediate reaction product (here represented as MnOOH*) which subsequently reacts with sorbed (COO)2-2 to form an unreactive Mn(III)-oxalate surface complex at the solution-mineral interface according to the reactions: 2MnO2+(COO)2-2+2H+=2MnOOH*+2CO2↑ (1) 2MnOOH*+(COO)2-2=2[MnOOH-COO]- (2) X-ray Photoelectron Spectroscopy (XPS) results from Mn2p3/2, C1s and O1s spectra of reacted surfaces reveal that initially rapid production of CO2 via Eqn. (1) results in accumulation of CO2 at the reaction interface. After about 15 min, the reaction rate decreases to the point where CO2 desorption keeps pace with accumulation. Surface concentrations of CO2 suggest that the rate of CO2 production decreases with time, until after 10 hr of reaction, it is undetectable. Reduction of Mn(IV) to Mn(III) suggests that the MnO2-oxalate redox reaction proceeds as a transfer of one electron per metal centre.There is no XPS evidence for reduction of Mn(III) from birnessite to Mn(II) in the presence of oxalate. Although this reaction proceeds in presence of arsenite, it is inhibited by oxalate, probably through formation of a strong Mn(III)-oxalate surface complex (either monodentate or bidentate). This hypothesis is consistent with Mn3+(aq) stabilization by oxalate in aqueous solutions. Further study using X-ray absorption spectroscopy (XAS) is required for a better understanding of the structure of the surface complexes.Rate of release of soluble Mn(II) to dilute oxalate solutions (5 x 10-4 M) is lower by an order of magnitude than the rate of release to aerated, distilled water at similar pH. Apparently, the process of proton-promoted dissolution of the soluble Mn(II) component of birnessite in distilled water is impeded by the addition of oxalate, probably by formation of a binuclear, bidentate surface complex between Mn(II, III) and adsorbed oxalate ions.